MAKTABGAChA YOSh DAVRIDAGI BOLALARDA XAVOTIRLANIShNING ZAMONAVIY KOʻRINIShLARI VA ULARNING PSIXOLOGIK YEChIMLARI - Xasanova, S.G. (SCIENCE and SOCIETY, 2025)
At preschool age, children experience various emotional and psychological states. Anxiety, while in one of these states, plays an important role in children’s self-expression, social relationships, and educational processes. In this article, we will talk about modern manifestations of anxiety in preschoolers and measures to reduce them.